Tuning Gaps and Schottky Contacts of Graphene/Phosphorene Heterostructures by Vertical Electric Field and Strain - Alessia Muroni; Simone Brozzesi; Friedhelm Bechstedt; Paola Gori; Olivia Pulci (Nanomaterials, 2023)
We present a comprehensive study of the structural and electronic properties of a graphene/phosphorene (G/P) heterostructure in the framework of density functional theory, including van der Waals interaction in the exchange–correlation functional. While the G(4 × 1)/P(3 × 1) superlattice usually used in the literature is subject to a strain as high as about 7%, the in-plane strain could be drastically reduced to under 1% in the G(4 × 13)/P(3 × 12) heterostructure investigated here. Adapting the lattice constants of the rectangular lattices, the equilibrium configuration in the xy plane of phosphorene relative to the graphene layer is optimized. This results in an equilibrium interlayer distance of 3.5 Å and a binding energy per carbon atom of 37 meV, confirming the presence of weak van der Waals interaction between the graphene and the phosphorene layers. The electronic properties of the heterostructure are evaluated under different values of interlayer distance, strain and applied vertical electric field. We demonstrate that G/P heterostructures form an n-type Schottky contact, which can be transformed into p-type under external perturbations. These findings, together with the possibility to control the gaps and barrier heights, suggest that G/P heterostructures are promising for novel applications in electronics and may open a new avenue for the realization of innovative optoelectronic devices.